Taxonomic changes in Bostrichidae (Insecta, Coleoptera) - Jerzy, Borowski (Zootaxa, 2022)
The taxonomic changes concern 6 species belonging to the family Bostrichidae. After a taxonomic analysis the following synonyms were established: Melalgus japonicus Chûjô, 1973 n. syn. of M. batillus (Lesne, 1902), Amphicerus (C.) malayanus (Lesne, 1898) n. syn. of A. (C.) caenophradoides (Lesne, 1895), Bostrychoplites megaceros Lesne, 1899 n. syn. of Bostrychoplites cornutus (Olivier, 1790), Bostrychoplites suturalis Lesne, 1931 n. syn. of Bostrychoplites peltatus Lesne, 1899, Lichenophanes fasciculatus (Fall, 1909) n. syn. of Lichenophanes penicillatus (Lesne, 1895), and Megabostrichus imatadei Chûjô, 1964 n. syn. of Phonapate stridula Lesne, 1909. The new synonymy results from a study of typical specimens as well as from latest publications concerning the taxonomy of this insect group.